Marriage Readiness among Final-Year University Students: The Role of Emotional Maturity and Interpersonal Communication Skills as Predictive Factors - Aprilia Setyowati; Diki Herdiansyah; Siti Muyana; Irvan Budhi Handaka; Corry Ardinana; Mufied Fauziah (Department of Guidance and Counseling, FIP, Undiksha, 2026)
Marriage readiness is an essential developmental task in early adulthood, yet many final-year students face the transition to marriage without adequate psychological and interpersonal preparedness. Empirical research that comprehensively identifies personal competencies as predictors of marriage readiness in this transitional phase remains limited. This study aims to analyze and examine the predictive role of emotional maturity and interpersonal communication skills on marriage readiness among final-year students. A correlational quantitative design was employed with unmarried final-year students selected through purposive sampling. Data were collected using an emotional maturity scale based on emotional regulation and stability, the Interpersonal Communication Competence Scale (ICCS), and a marriage readiness scale covering psychological, emotional, social, and marital value dimensions. Multiple regression analysis was conducted after testing statistical assumptions, validity, and reliability. The results indicate that both emotional maturity and interpersonal communication skills are significant predictors of marriage readiness, with interpersonal communication showing a relatively stronger contribution. These findings underscore the importance of developing emotional regulation and interpersonal communication competence as essential components of interventions aimed at preparing students for marital life.